Determinants of the duration and ending of terrorist and other non-state armed groups - Dominik Noe (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2013)
This study empirically investigates the impact of group characteristics and host country conditions on the duration and the ending of terrorist organizations and rebel groups. The empirical analysis relies on data for more than 600 armed groups from the Terrorist Organization Profiles, collected by the MIPT, and employs discrete time duration models with unobserved heterogeneity and its application to a setting with competing risks. It is found that organizations stabilize over time and face the highest risk of failure at the beginning. Factors that motivate members play an important role, as does support from other countries. Rich states are more likely to defeat armed groups and there is no evidence found that a restriction of civil rights decreases the duration of armed groups or increases the likelihood of capturing them.
Keywords: H56; D74; H39; 330; Terrorist organizations; Insurgency; Duration analysis; Discrete time duration model; Competing risk regression; Civil war